2011
DOI: 10.1161/strokeaha.110.602888
|View full text |Cite|
|
Sign up to set email alerts
|

Does Treatment of Ruptured Intracranial Aneurysms Within 24 Hours Improve Clinical Outcome?

Abstract: Background and Purpose-The purpose of this study was to analyze whether treating ruptured intracranial aneurysms within 24 hours of subarachnoid hemorrhage improves clinical outcome. Methods-An 11-year database of consecutive ruptured intracranial aneurysms treated with endovascular coiling or craniotomy and clipping was analyzed. Outcome was measured by the modified Rankin Scale at 6 months. Our policy is to treat all cases within 24 hours of subarachnoid hemorrhage. Treatment delays are due to nonclinical lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 58 publications
5
75
0
7
Order By: Relevance
“…However, for treatment within 24 hours, it has been shown that this timeframe was associated with improved clinical outcomes, although the benefit was more pronounced for coiling than clipping. 34 Moreover, it is unlikely that the risks of acute treatment will accrue in such a way that they outweigh the very high morbidity and mortality rates associated with rebleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for treatment within 24 hours, it has been shown that this timeframe was associated with improved clinical outcomes, although the benefit was more pronounced for coiling than clipping. 34 Moreover, it is unlikely that the risks of acute treatment will accrue in such a way that they outweigh the very high morbidity and mortality rates associated with rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…34 Recognizing risk factors for aneurysmal rebleeding is particularly relevant and might help to identify the aneurysms that benefit from acute treatment. In recent years, several risk factors, such as hypertension and the location and size of the aneurysm, have been shown to be associated with rebleeding.…”
mentioning
confidence: 99%
“…Subarachnoid hemorrhage (SAH) is frequently associated with significant morbidity and mortality, especially when the diagnosis is missed (1,2). Unfortunately, initial presenting symptoms of this disease are frequently subtle and often overlap with more common and more benign headaches.…”
Section: Introductionmentioning
confidence: 99%
“…2 Nevertheless, a diagnosis of aneurysmal SAH should never be missed, because early diagnosis and treatment of aneurysmal SAH are associated with better functional outcomes. 3 Common practice for diagnostic evaluation of patients suspected of having SAH is a head CT and a subsequent lumbar puncture for cerebrospinal fluid (CSF) analysis if head CT is negative or inconclusive. 4,5 A recent study suggested that a lumbar puncture is not needed if a thirdgeneration head CT scan performed within 6 hours after headache onset and interpreted by a qualified radiologist excludes the presence of blood in the subarachnoid space.…”
mentioning
confidence: 99%